Therapeutic Value of Medicinal Mushroom Agaricus blazei Murill - Mehwish Murad Ali; Mirza Tasawer Baig; Muhammed Aslam; Uzma Shahid; Aisha Jabeen (ziauddin University, 2024)
Agaricus blazei Murill (AbM) is a mushroom that has been utilized in alternative drug to anticipate cardiac disease, diabetes, arthritis, increased cholesterol, cancer, hepatitis and cancers. It contains β-glucan, which contributes to decreasing blood sugar in-vivo and acts against cancer. The extract of this mushroom exerts antioxidant action in-vivo. AbM contains agaritine that exerts antitumor effects against leukemic cells in vitro. This mushroom is also found to have immune-stimulatory function, tumor growth suppression, action against allergy, antiviral effects, antimicrobial function and immune modulatory effects. Researchers also studied its action in decreasing blood cholesterol. According to several studies, AbM containing (1→6)-β-D-glucan-exerts anti angiogenesis action. The purpose of this extensive review on the medicinal value of AbM mushroom was to highlight its significance and its traditional uses by scientific evidence to determine the effectiveness of the mushroom in various evidence-based uses. Google Scholar and PubMed search engines were used to browse articles from 1994-2019 on the therapeutic value of AbM. Initially, 74 articles were found related to the therapeutic value of AbM. After reviewing the available article, 42 were selected based on the medicinal uses of AbM. It was concluded that AbM possessed various bioactive compounds that are responsible for its therapeutic effects. Keywords: Mushroom; Antidiabetic; Therapeutics.